One-pot synthesis of highly fluorescent Fe2+-doped carbon dots for a dual-emissive nanohybrid for the detection of zinc ions and histidine. (20th July 2018) - Han, Bingyan; Peng, Tingting; Yu, Mingbo; Chi, Chen; Li, Ying; Hu, Xixi; He, Gaohong
Abstract : Fe 2+ was confirmed to be the only definitive one of the common metal ions to synthesize the highly fluorescent carbon dots with proline as the carbon resource at 80 °C for visual fluorescence sensing Zn2+ and histidine, respectively. Abstract : Metal ion-doping has been paid little attention for improving the fluorescence intensity of carbon dots (CDs) compared with nonmetallic-element doping. Herein, for the first time, Fe 2+ -doped CDs were facilely synthesized at 80 °C instead of by a hydrothermal method. Fe 2+ was confirmed to be the only definitive common metal ion to synthesize highly fluorescent CDs with proline (Pro) as a carbon resource. The as-synthesized Fe 2+ -doped CDs showed bright blue fluorescence at 455 nm and exhibited favorable anti-ion, pH, and time stability. The blue cysteine-functional-Fe 2+ -doped CDs were combined with red gold nanoclusters (Au NCs) to construct a nanohybrid by electrostatic interaction for the ratiometric fluorescence sensing of Zn 2+ and histidine (His), in which the CDs acted as a reference signal and the Au NCs as an analyte-responsive unit. The detection of Zn 2+ and histidine (His) was shown by two distinct blue-pink and pink-blue-pink fluorescence color changes, respectively. Both of them showed excellent selectivity and sensitivity. Dual-emission fluorescent probes avoid the shortcomings of single fluorescence signals, which are susceptible to experimental conditions, and have a bright future being utilized for the visual detection of Zn 2+ and His in practical analysis.